Unveiling the Molecular Symphony: Exploring Mechanisms, Diversity and Applications of Restriction Enzymes in Biology - Abdulsalam, Mustapha; Hamza, Fatima Umar; Saddeeq, Fatima Abubakar; Ibrahim, Hafsa Hamisu; Dutse, Hafsa Ahmad Isa-; Falaki, Aisha Mustapha (MultiTech Publisher, 2024)
This research delves into the multifaceted role of restriction enzymes in molecular biology, examining their historical evolution, intricate mechanisms, and diverse applications. It aims to comprehensively understand their versatility and integration with modern technologies like CRISPR-Cas9, particularly in personalized medicine and gene therapy. Addressing a research gap in the synergism of restriction enzymes with CRISPR-Cas9 and their role in epigenetic modifications, qualitative methods critically assess existing literature and propose future research models. Findings highlight the potential for enhancing genome editing precision and exploring epigenetic alterations involving restriction enzymes, shedding light on DNA methylation, histone modification, and gene expression interplay. Recommendations stress incorporating restriction enzymes in epigenetic studies, offering insights into disease research, personalized medicine, and gene therapy precision. This research contributes to the wealth of discoveries in molecular biology, paving the way for future breakthroughs and deeper insights.